Métodos alternativos para proteção à corrosão da liga de alumínio 2024-T3 - Xavier, Thiago Henrique Andrade [UNIFESP] (2015)
This work presents the anti-corrosion behavior of a soluble copolymer of polyaniline (PAni), called poly (phenylene sulfide phenylamine) - PPSA, deposited on the Al 2024-T3 alloy. The motivation for the use of this copolymer is that it shows electroactivity similar to PAni, but it is soluble in various organic solvents, allowing its deposition by casting. Additionally, the anti-corrosion performance of polypyrrole (PPy) electrodeposited in ionic liquid was also studied. The use of ionic liquid as electrolyte was motivated because the Al alloy is not corroded in this medium. The efficiency of PPSA and PPy films in the corrosion protection of Al 2024-T3 alloy was investigated by open circuit potential tests, potentiodynamic polarization curves, electrochemical impedance spectroscopy, immersion tests and scanning electron microscopy. The PPSA film, in reduced form, produced with six subsequent depositions of its solution in tetrahydrofuran (4 mg/mL) resulted in the best performance against corrosion. Thicker films do not show satisfactory results due to their lower adhesion on the Al alloy. The PPSA film with six depositions was more compact and homogeneous, which afforded better performance in the corrosion protection, probably preventing the penetration of aggressive species, such as chloride ions. The PPy was efficiently electrodeposited on the Al 2024-T3 alloy by cyclic voltammetry. The morphology of this film was dependent on the scan rate used. The micrographs showed that in all experimental conditions, the films are quite porous, giving low efficiency of these coatings in the corrosion protection of the alloy.